The role of immunology in the etiopathogenesis, diagnosis and treatment of endometriosis - Sérgio Podgaec; Mauricio Simões Abrão (Einstein (São Paulo), 2005)
Presently, several endometriosis features are subject of researchdue to some gaps that remain concerning the actual origin of thisdisease. If one could find out how endometrial tissue implants inextrauterine sites, its diagnosis and treatment would advancesignificantly. One of the leading investigations focus onimmunological issues, since different cells and cytokines takepart in cellular and humoral immune response in the developmentof endometriosis. This article proposes an updated review of therelation between endometriosis and immunology and brings newclinical perspectives for disease management.